Assays for phenotypic and functional characterization of cryopreserved platelets. (2nd January 2019) - Marks, Denese C; Johnson, Lacey
Abstract: Platelet concentrates for transfusion have a limited shelf-life, and cryopreservation offers a means of extending platelet shelf-life for at least 2 years. Cryopreservation, however, has some disadvantages, as platelets can be damaged during the freezing and thawing process. Consequently the phenotype of cryopreserved platelets is very different to that of freshly collected, liquid stored platelets. To obtain a reliable overview of cryopreserved platelet quality and function, specific testing methodologies should be considered. Whilst light transmission aggregometry (LTA) is the gold standard for measuring in vitro platelet reactivity in liquid stored platelets, it is not suited for cryopreserved platelets, as they retain little response to typical platelet agonists, even at high doses. Instead, phenotypic characterization by flow cytometry in combination with global assays of coagulation provides a clearer delineation of the phenotype and function of cryopreserved platelets. With increasing international uptake of platelet cryopreservation, it is important to recognize the need for appropriate measures of platelet quality and function.